Influence of organic and chemical fertilization on the yield of flowers, contents and composition of essential oil of (Chamomilla recutita (L.) Rauschert) - Corrêa, C.; Castellane, P. D. [UNESP]; Jorge Neto, J. [UNESP] (My University, 1999)
A field experiment was conducted with chamomile (Chamomilla recutita [L.] Rauschert), in an area of the Olericulture and Medicinal Plants of the Horticulture Department at UNESP - Jaboticabal Campus, with the aim to evaluate the influence of organic and chemical fertilization on the yield of flowers, and content and composition of the essential oil of chamomile. The experimental design for the yield of flowers consisted of randomized blocks with 7 treatments and 4 replications, for the analysis of the contents and composition of the oil, the completely randomized block was used and for analysis of the correlation between harvesting and treatment, the split-plot design into randomized blocks was used. The treatments tested were: no fertilization, green manure (Mucuna aterrima + Crotalaria spectabilis), green manure (plant cocktail), organic fertilizer (farmyard manure), N as urea, N as ammonium sulphate, NPK with N supplement as ammonium sulphate. There was no influence of the treatments on the yield of flowers nor on the essential oil content; on the other hand both characteristics did show significant differences in harvesting times (Tukey 5%). The main yield was 885.90 kg/ha dry flowers and the mean oil content was 0,86%. The green manure treatment (M. aterrima + C. spectabilis) showed a higher percentage of chamazulene content, with a highly significant difference in harvesting times (Tukey 1%). The a-bisabolol percentages did not evidence significant differences between treatments. However, among harvesting times, there was a variation. A negative correlation was verified between the chamazulene and abisabolol percentages; the first increasing - from 21.02 to 36.17% - and the latter decreasing - from 14.12 to 8.72 % - from the first to the sixth harvest. The observed mean content of chamazulene was 14.64 % and a-bisabolol was 16.72 %.
Keywords: α-bisabolol; Chamazulene; Chamomile (Chamomilla recutita); Essential oil; Fertilization; Manure